Seismic Performance of Exterior Steel Ring-Stiffener Joint - Zhaoqiang Zhang; Yanru Sa; Yong Yao; Junhai Zhao (Advances in Civil Engineering)
We study the seismic performance of the exterior steel ring-stiffener (ESRS) joint, a member that is used to connect a steel beam to a square steel tubular column filled with steel fibre recycled concrete for seismic resistance. To this end, the influence of seismic factors such as axial compression ratio and beam-column linear stiffness ratio on seven specimens is studied. A physical test is conducted on the specimens with a series of cyclic loadings. The testing and analysis of hysteretic loops and skeleton curves of the ESRS joints revealed the seismic performance characteristics including failure mode, rigidity, ductility, bearing-capacity degradation, and energy dissipation capacity. The results reveal (a) damage to the specimens at the beam-end near the joint, (b) no failure at the joints’ core area and column, (c) appearance of a plastic hinge at the beam-end near the joint, and (d) plump spindle-shaped hysteretic loops and normal rigidity degradation curves in the specimens. The specimens are then simulated with the finite element method (FEM) and the results are compared with those of the physical test.